2019
DOI: 10.18261/issn.1891-943x-2019-01-02-02
|View full text |Cite
|
Sign up to set email alerts
|

Involvement with Response Technology as Student-Centringof Language Teaching

Abstract: Response technology (RT) is frequently applied to engage students in education, but research on RT has only perfunctorily studied student involvement in decision-making in secondary education. Because such research is also scarce in language learning, this study aimed to identify and examine how students and teachers experience studentcentring of language teaching through RT-mediated involvement. A qualitative-dominant, mixed-methods case study design provided data through observations, interviews, and surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Science-math stories and other supporting contents are made in the form of application software with the ".apk" format titled "Citraloka Adventure" which can be used on Android type mobile devices. The use of digital technology is considered as saving money, saving time, and providing useful information so that it impacts people's habits or way of life [27]. The development of cellular technology in people's lives has the potential for new teaching and learning patterns [18].…”
Section: Fig 1 Initial Display Of Digital Learning-based On Science-mathmentioning
confidence: 99%
“…Science-math stories and other supporting contents are made in the form of application software with the ".apk" format titled "Citraloka Adventure" which can be used on Android type mobile devices. The use of digital technology is considered as saving money, saving time, and providing useful information so that it impacts people's habits or way of life [27]. The development of cellular technology in people's lives has the potential for new teaching and learning patterns [18].…”
Section: Fig 1 Initial Display Of Digital Learning-based On Science-mathmentioning
confidence: 99%
“…In the article by Li et al (2019) marked the efficiency of interdisciplinary cooperation between language professionals and experts in the study of a foreign language scholars. The research by Einum (2019) demonstrated the effectiveness of Response Technology (RT) in learning the foreign language. The article of Velinova (2019) discusses modern interactive methods of teaching the Bulgarian language at school.…”
Section: Literature Reviewmentioning
confidence: 99%